2020
DOI: 10.1002/hbe2.217
|View full text |Cite
|
Sign up to set email alerts
|

Interactional theory of childhood problematic media use

Abstract: The growth of mobile device access and ownership has yielded many opportunities and challenges for raising healthy digital media consumers. As adoption of mobile and internet-connected devices has increased among children, concerns for healthy child development have been expressed regarding excessive or problematic use. Although much theoretical and empirical work has been conducted evaluating adolescents' and adults' risks for dependence on various screen media (e.g., Gaming Disorder, Internet Addiction), lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 73 publications
(79 reference statements)
3
124
0
Order By: Relevance
“…Parents at different income levels were also facing different levels of stress during the pandemic, which could affect the family and media environments (Cluver et al, 2020). One of the distal factors in Domoff et al's (2020) IT-CPU is SES/poverty, and so families at lower levels of SES could have much different experiences of problematic media use compared to the families in the current sample given higher economic stress during the pandemic. These factors, taken together, mean that the findings are limited in generalizability due to the demographics and convenience nature of the sample.…”
Section: Limitations Future Research and Implicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Parents at different income levels were also facing different levels of stress during the pandemic, which could affect the family and media environments (Cluver et al, 2020). One of the distal factors in Domoff et al's (2020) IT-CPU is SES/poverty, and so families at lower levels of SES could have much different experiences of problematic media use compared to the families in the current sample given higher economic stress during the pandemic. These factors, taken together, mean that the findings are limited in generalizability due to the demographics and convenience nature of the sample.…”
Section: Limitations Future Research and Implicationsmentioning
confidence: 91%
“…Rather, these negative effects and associations stem from various factors: how the media are used, what the media are, the characteristics of the child using the media, and so on. Domoff et al, ( 2020 ) recently elucidated an Interactional Theory of Childhood Problematic Media Use (IT‐CPU), an extension of Bronfenbrenner's bioecological model that emphasizes the proximal, distal, and maintaining factors that can lead to the emergence of problematic media use. Distal factors, such as household chaos and digital environmental design, can exert their influence on proximal factors like a child's characteristics, parent media use and beliefs, and peer technology access.…”
Section: Problematic Media Usementioning
confidence: 99%
“…Specifically, McDaniel and Radesky ( 2017 ) revealed that parents introduce digital media to their toddlers or pre-schoolers during family activities such as meals, doctor visits, or car drives. Again challenging behaviors and emotional dysregulation have been shared by parents as reasons for young children’s problematic digital media use (Domoff, Borgen, & Radesky, 2020 ). A child’s gender is an important factor concerning access to digital tools and parental mediation of digital play.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing adolescents’ perceptions of their own problematic use may also be informative. Examining the mechanisms of influence (i.e., self-regulation deficits related to early disrupted attachment as well as those proposed by Domoff et al) is critical to inform intervention [ 21 ]. Including parental monitoring or other media parenting practices is also recommended as these variables may moderate the impact of ACEs on problematic media use.…”
Section: Discussionmentioning
confidence: 99%
“…Poor self-regulation has been found to be associated both with number of ACEs and increased problematic media use [ 13 , 20 ]. Other potential mechanisms associated with problematic media use include lack of household structure, poor child self-efficacy, and strained parent-child relationships [ 21 ]. Additionally, parenting stress has been found to mediate the association between ACEs and increased media use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%